2019
DOI: 10.1103/physrevlett.123.107701
|View full text |Cite
|
Sign up to set email alerts
|

Strong Coupling between Magnons and Microwave Photons in On-Chip Ferromagnet-Superconductor Thin-Film Devices

Abstract: We demonstrate strong magnon-photon coupling of a thin-film permalloy device fabricated on a coplanar superconducting resonator. A coupling strength of 0.152 GHz and a cooperativity of 68 are found for a 30-nm-thick permalloy stripe. The coupling strength is tunable by rotating the biasing magnetic field or changing the volume of permalloy. We also observe an enhancement of magnonphoton coupling in the nonlinear regime of the superconducting resonator, which is mediated by the nucleation of dynamic flux vortic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
144
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 188 publications
(155 citation statements)
references
References 58 publications
(79 reference statements)
9
144
1
1
Order By: Relevance
“…Regarding experimental implementations, while we have considered here a hybrid superconducting circuit with the ensembles of spins in diamond crystal coupled to the transmission line resonators (forming the Dicke model) [59][60][61][62][63][64], our proposal is not limited to this particular architecture and could be implemented or adapted in a variety of platforms, e.g., atomic [65,66], molecular [67], and ferromagnetic [68][69][70][71] systems coupled to superconducting cavities. For our specific design, considering an ensemble with N ∼ 10 12 spins and the single spin coupling λ 0 ∼ 10 Hz, an enhanced collective coupling λ ≈ √ Nλ 0 ∼ 10 MHz [59][60][61][62][63][64] allows our model to reach an ultrastrong-coupling regime, which demonstrates that the critical coupling of QPT can be readily realized with state-of-the-art technology.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding experimental implementations, while we have considered here a hybrid superconducting circuit with the ensembles of spins in diamond crystal coupled to the transmission line resonators (forming the Dicke model) [59][60][61][62][63][64], our proposal is not limited to this particular architecture and could be implemented or adapted in a variety of platforms, e.g., atomic [65,66], molecular [67], and ferromagnetic [68][69][70][71] systems coupled to superconducting cavities. For our specific design, considering an ensemble with N ∼ 10 12 spins and the single spin coupling λ 0 ∼ 10 Hz, an enhanced collective coupling λ ≈ √ Nλ 0 ∼ 10 MHz [59][60][61][62][63][64] allows our model to reach an ultrastrong-coupling regime, which demonstrates that the critical coupling of QPT can be readily realized with state-of-the-art technology.…”
Section: Discussionmentioning
confidence: 99%
“…On-chip implementation and integration of quantum magnonic systems are highly desirable for circuit-based applications and building up complex networks of coupled magnonic systems. 21,22 One direct approach is to integrate magnetic devices with coplanar superconducting resonators, 11,[23][24][25][26][27] which can carry long-coherence microwave photons and couple with superconducting qubits for building up circuit quantum electrodynamics (cQED).…”
Section: A Magnon-photon Coupling and Superconducting Resonatorsmentioning
confidence: 99%
“…(1), in order to increase g with a limited magnetic device volume V M (or N ), it is important to have a small V c , which leads to a large coupling strength per Bohr magneton defined as g 0 = g/ √ N . Recently, Li et al 25 and Hou et al 26 have demonstrated strong magnon-photon coupling between permalloy (Ni 80 Fe 20 , Py) thin-film devices and coplanar superconducting resonators. As shown in Figs.…”
Section: A Magnon-photon Coupling and Superconducting Resonatorsmentioning
confidence: 99%
“…To date, both magnon–photon and magnon–magnon couplings are predominantly investigated by the cavity ferromagnetic resonance (FMR) spectroscopy, i.e. microwave transmission and/or reflection measurements, typically involving a vector-network analyzer (VNA) or a microwave diode 5 , 7 13 , 30 33 , 35 . Strong magnon–magnon couplings have been observed in yttrium iron garnet (Y Fe O , YIG) coupled with ferromagnetic (FM) metals, where exchange spin waves were excited by a combined action of exchange, dampinglike, and/or fieldlike torques that are localized at the interfaces 30 33 .…”
Section: Introductionmentioning
confidence: 99%